Preparation and properties of porous TaC foam ceramic filter - Qiao Yu; Wei Sun; Tian Tian; Junjie Xu; Yuzhu Shen; Xiang Xiong (Journal of Materials Research and Technology)
To effectively prevent the contamination of carbon particle volatiles during the preparation of high-purity SiC crystals using the physical vapor transport method (PVT) in ultra-high temperature environments (T ≥ 2000 °C), this paper innovatively employs a low-cost and easily controllable organic foam impregnation method to prepare porous TaC foam ceramics (PTC) for filtering high-temperature gases. This study systematically investigates the effects of variations in components such as binders and sintering aids in the ceramic slurry on the microstructure and compressive strength of PTC, and analyzes the corrosion behavior of PTC in high-temperature gases of Si, Si2C, and SiC2. The results indicate that a ceramic slurry containing 0.4 wt% carboxymethyl cellulose (CMC) can achieve high coating ability and stability for TaC ceramic slurry. During the initial 10 h of standing sedimentation, no sedimentation or agglomeration phenomena were observed in the ceramic slurry. The PTC obtained with the addition of 0.7 wt% Co sintering aid exhibited the best structural characteristics, with tightly bonded grains, fewer internal pores, a porosity of up to 80.06 %, and a compressive strength of 2.56 MPa. PTC-Co demonstrated good corrosion resistance, with its main component still being TaC, experiencing a mass loss of approximately 1.45 %, effectively blocking the diffusion of carbon particles and efficiently filtering high-temperature gases of Si, Si2C, and SiC2.